Karaganda region, the main cancer — causing factors in the geographic view In the years of census, 1999–2009 - Кеnzhina, K.D.; David, L.; Toimbekova, K.S. (Fundamental and Experimental Biology, 2016)
The article shows that many factors affect negatively in our time on the demographic situation. Among them are the main ones: Economic, social, political, etc. But, in recent years the influence of environmental factors on the same situation, is considered versatile and determined extent of their influence. Achieving this goal can give the opportunity to open further ways of their solution.